DAMPAK KEBIJAKAN PEREKONOMIAN ERA ORDE BARU - Rafan Fadhlurrahman; Salman Badawi (Yayasan Gema Bina Nusantara, 2023)
Various scholars and linguists have examined pragmatics as a concept. The fundamental problem associated with description, definition or explanation in terms of acceptance is that there is no universality (Levinson, 2009). Pragmatics as a concept is not a distinction. Addressing some insights about what is meant by pragmatics and what it reflects is a view of its scope. Gadzar (1979, p. 2) is of the view that